Research on performance of jet refrigeration cycle driven by waste heat of refrigerated vehicle - Jiang, Shujun; Pan, Xiubin; Zhang, Song; Huang, Yanmei; Que, Wenshuai; Sang, Hailang; Guan, Wei (Frontiers in Energy Research, 2024)
Nowadays, refrigerated food storage and transport vehicles are very common. However, with regard to the engine of vehicles, a significant amount of heat is discharged into the environment in the form of exhaust gas and jacket water. If the cooling system is used to convert this waste heat into cooling capacity, the thermal efficiency of the engine will be improved to a certain extent. Therefore, this paper uses two waste heat recovery jet refrigeration systems to recover heat from the exhaust gas and jacket water of the refrigerated vehicle. One is a conventional jet refrigeration system that uses only engine exhaust as the heat source, and the other is a system that adds a preheater upstream of the generator based on the conventional system, using engine jacket water to preheat the working fluid. This paper presents the results of comparing the impact of R141b/R123, R141b/R245fa, R142b/R134a, and R142b/R152a working fluids on system performance, and considers the effects of operating temperature and secondary flow pressure drop in the ejector receiving chamber on the system performance. The research results indicate that of the four selected working fluids, the R141b/R245fa (0.4/0.6) blend has the best overall performance. After the addition of a preheater, the system using R142b/R134a (0.6/0.4) hybrid working fluid achieves the maximum cooling capacity of 16.0994 kW and the maximum thermal efficiency of 5.45%, and the exergy loss in the generator is 1 kW lower than without the preheater.